Control of Tribological Characteristics of Wear-Resistant AlCrBN Coatings by Nanoscratch Testing - V. A. Lapitskaya; T. A. Kuznetsova; B. Warcholinski; A. V. Khabarova; T. V. Hamzeleva; A. Gilewicz; S. A. Chizhik (Приборы и методы измерений)
In recent years, high-precision probe methods have been increasingly used to control the surface microstructure, mechanical and tribological properties of coatings instead of standard methods. The aim of the work was to study the tribological characteristics of the wear-resistant coatings (using the example of AlCrBN coatings deposited with changes in nitrogen pressure, substrate bias voltage and cathode current) at the microand nanolevel using the nanoscratch testing (nano-scratching) method. The nanoscratch testing method is a non-standard method of tribotesting the wear-resistant coatings and is based on the reciprocating movement of a spherical diamond indenter with a curvature radius of 226 nm on the surface (under a certain load). It was found that the friction coefficient decreases from 0.087 to 0.036 for coatings deposited with an increase in pressure from 2 to 5 Pa. When the bias voltage on the substrate changes from -50 to -150 V, the friction coefficient decreases from 0.077 to 0.041 and when the cathode current changes from 80 to 100 A, the friction coefficient remains virtually unchanged. The use of this method made it possible to perform multi-cycle tribotesting of the AlCrBN coatings, determine the average values of the friction coefficient, and completely eliminate the influence of microparticles (the characteristic defects for coatings deposited by the cathodic arc method) on the measurements. Thus, the effectiveness of the nanoscratch testing (nanoscratching) as a method for the control wear-resistant coatings is demonstrated.